Endosomal-Lysosomal Processing of Neurodegeneration-Associated Proteins in Astrocytes - Ching-On Wong (International Journal of Molecular Sciences, 2020)
Most common neurodegenerative diseases (NDs) are characterized by deposition of protein aggregates that are resulted from misfolding, dysregulated trafficking, and compromised proteolytic degradation. These proteins exert cellular toxicity to a broad range of brain cells and are found in both neurons and glia. Extracellular monomeric and oligomeric ND-associated proteins are taken up by astrocytes, the most abundant glial cell in the brain. Internalization, intracellular trafficking, processing, and disposal of these proteins are executed by the endosomal-lysosomal system of astrocytes. Endosomal-lysosomal organelles thus mediate the cellular impact and metabolic fate of these toxic protein species. Given the indispensable role of astrocytes in brain metabolic homeostasis, the endosomal-lysosomal processing of these proteins plays a fundamental role in altering the trajectory of neurodegeneration. This review aims at summarizing the mounting evidence that has established the essential role of astrocytic endosomal-lysosomal organelles in the processing of amyloid precursor proteins, Apolipoprotein E (ApoE), tau, alpha synuclein, and huntingtin, which are associated with NDs such as Alzheimer’s, Parkinson’s, and Huntington diseases.